Engagement and contestation: The entangled imagery of the Silk Road. (1st March 2018) - Dadabaev, Timur
Abstract: There is considerable debate over how and in what form Central Asian (CA) states should conduct relations among each other and with other post-Soviet states. The notion of the "Silk Road" has become one of the symbols of extended economic and political cooperation. Notably, however, Japan (Silk Road Diplomacy, 1996–1999), China (One Belt, One Road [OBOR] or the Belt and Road initiative [BRI]) and South Korea (Silk Road Strategy, 2011) have used the rhetoric of reviving the Silk Road to imply closer engagement with the CA region but with different connotations. This paper focuses on the formation of this discourse of engagement with the CA region through the notion of the Silk Road in China, South Korea and Japan and raises the following questions: What are the approaches that facilitate the most effective ways of engaging CA states under this "Silk Road" rhetoric? What are the principles that have detrimental effects on the successes and failures of the engagement of China, Japan and South Korea? The primary objective of this paper is to address these questions and to stimulate debate among both academics and policy makers on the formats of engagement and cooperation in Eurasia.